Health and social determinants and outcomes of home cooking: A systematic review of observational studies. (1st April 2017) - Mills, Susanna; White, Martin; Brown, Heather; Wrieden, Wendy; Kwasnicka, Dominika; Halligan, Joel; Robalino, Shannon; Adams, Jean
Abstract: Many dietary interventions assume a positive influence of home cooking on diet, health and social outcomes, but evidence remains inconsistent. We aimed to systematically review health and social determinants and outcomes of home cooking. Given the absence of a widely accepted, established definition, we defined home cooking as the actions required for preparing hot or cold foods at home, including combining, mixing and often heating ingredients. Nineteen electronic databases were searched for relevant literature. Peer-reviewed studies in English were included if they focussed mainly on home cooking, and presented post 19 th century observational or qualitative data on participants from high/very high human development index countries. Interventional study designs, which have previously been reviewed, were excluded. Themes were summarised using narrative synthesis. From 13, 341 unique records, 38 studies – primarily cross-sectional in design – met the inclusion criteria. A conceptual model was developed, mapping determinants of home cooking to layers of influence including non-modifiable, individual, community and cultural factors. Key determinants included female gender, greater time availability and employment, close personal relationships, and culture and ethnic background. Putative outcomes were mostly at an individual level and focused on potential dietary benefits. Findings show that determinants of home cooking are more complex than simply possessing cooking skills, and that potential positive associations between cooking, diet and health require further confirmation. Current evidence is limited by reliance on cross-sectional studies and authors' conceptualisation of determinants and outcomes.